Empire express building the first transcontinental railroad - Bain, David Haward (Penguin Books, 2000)
Chronicles the events that took place in the thirty years it took to complete the first transcontinental railroad, profiling the key players in its development, the major setbacks the workers faced, and the public objections to the railroad's completion.